Scale effect in a LUTI model of Brussels: challenges for policy evaluation - Jones, Jonathan; Peeters, Dominique; Thomas, Isabelle (European Journal of Transport and Infrastructure Research, 2017)
The aim of this paper is to assess the reliability of policy evaluation based on Land Use and Transport Interactions models, relative to the choice of the Basic Spatial Units. An UrbanSim (+ MATsim) model applied to Brussels (Belgium) is used as the case study. The evolution of the study area over twenty years is forecasted for four levels of Basic Spatial Units and five scenarios (businessas-usual and four alternatives). Results show larger variations between Basic Spatial Units levels than across scenarios. These findings are valid for various sustainability indicators and for a simple cost-benefit analysis aiming at ranking the scenarios. The direction of the variations resulting from the implementation of the scenarios remains, however, the same for all Basic Spatial Units levels. Hence, the influence of the scale on policy evaluation based on Land Use and Transport Interactions models appears limited when it is only intended to compare scenarios, but it will have a crucial role when evaluations are based on absolute variations or threshold values.